Fast calculation of spectral optical properties and pigment content detection in human normal and pathological kidney - Botelho, Ana R.; Silva, Hugo Filipe; Martins, Inês Soraia; Carneiro, Isa C.; Carvalho, Sónia D.; Henrique, Rui M.; Tuchin, Valery V.; Oliveira, Luís Manuel (Spectrochimica acta. Part A : Molecular and biomolecular spectroscopy)
A fast calculation method was used to obtain the spectral optical properties of human normal and pathological (chromophobe renal cell carcinoma) kidney tissues. Using total transmittance, total reflectance and collimated transmittance spectra acquired from ex vivo kidney samples, the spectral optical properties of both tissues, namely the absorption, the scattering and the reduced scattering coefficients, as well as the scattering anisotropy, dispersion and light penetration depth, were calculated between 200 and 1000 nm. Analysis of the mean absorption coefficient spectra of the kidney tissues showed that both contain melanin and lipofuscin, and that 83 % of the melanin in the normal kidney converts into lipofuscin in the pathological kidney.